AMC Brake Pad Engineering: The Role of Reinforcement, Silica Sand, and Boiler Fly Ash on Friction Coefficient and Density - Erwansyah, Erwansyah; Sukanto, Sukanto; Budi, Abdul; Wanto, Agus; Syahrizal, M. Razeev (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Innovations in making non-asbestos brake linings are increasingly being developed, asbestos materials which are less friendly to the environment and health are the main factors. This research utilizes recycled aluminum as a matrix and boiler fly-ash and silica sand as reinforcement. The aim of this research process is to determine the differences in variations in hot compaction pressure and powder volume percentage on shrinkage values and friction coefficients. The method used is the powder metallurgy method which includes mechanical alloying, hot compaction pressing and sintering. Mechanical Alloying is carried out using a ball mill machine with Ball Parameter-weight of Ratio (BPR) parameters of 10:1, rotational speed of 90 rpm, holding time of 6 hours with variations in the matrix percentage of 86%, 90%, 94% and the results of the mechanical alloying  will be weighed in variations, namely 25 gr. , 35 gr, and 45 gr. ASTM B962-17 density test and ASTM G99-05 coefficient of friction or wear test. The results obtained were the highest density value of 2.055 gr/cm3 with a reinforcement percentage of 94% compaction of 5600 Psi. The lowest density value is 1.848 gr/cm3 with a reinforcement percentage of 86% compaction of 5600 Psi. The friction coefficient test value is 0.147 gr with a reinforcement percentage of 86%, the powder weight is 45 gr. The lowest value of the friction coefficient test was 0.020 gr using a reinforcement percentage of 94% and a powder weight of 35 gr.